from sympy.core.numbers import (I, nan, oo, pi) from sympy.core.relational import (Eq, Ne) from sympy.core.singleton import S from sympy.core.symbol import (Symbol, symbols) from sympy.functions.elementary.complexes import (adjoint, conjugate, sign, transpose) from sympy.functions.elementary.miscellaneous import sqrt from sympy.functions.elementary.piecewise import Piecewise from sympy.functions.special.delta_functions import (DiracDelta, Heaviside) from sympy.functions.special.singularity_functions import SingularityFunction from sympy.simplify.simplify import signsimp from sympy.testing.pytest import raises from sympy.core.expr import unchanged from sympy.core.function import ArgumentIndexError x, y = symbols('x y') i = symbols('t', nonzero=True) j = symbols('j', positive=True) k = symbols('k', negative=True) def test_DiracDelta(): assert DiracDelta(1) == 0 assert DiracDelta(5.1) == 0 assert DiracDelta(-pi) == 0 assert DiracDelta(5, 7) == 0 assert DiracDelta(x, 0) == DiracDelta(x) assert DiracDelta(i) == 0 assert DiracDelta(j) == 0 assert DiracDelta(k) == 0 assert DiracDelta(nan) is nan assert DiracDelta(0).func is DiracDelta assert DiracDelta(x).func is DiracDelta # FIXME: this is generally undefined @ x=0 # But then limit(Delta(c)*Heaviside(x),x,-oo) # need's to be implemented. # assert 0*DiracDelta(x) == 0 assert adjoint(DiracDelta(x)) == DiracDelta(x) assert adjoint(DiracDelta(x - y)) == DiracDelta(x - y) assert conjugate(DiracDelta(x)) == DiracDelta(x) assert conjugate(DiracDelta(x - y)) == DiracDelta(x - y) assert transpose(DiracDelta(x)) == DiracDelta(x) assert transpose(DiracDelta(x - y)) == DiracDelta(x - y) assert DiracDelta(x).diff(x) == DiracDelta(x, 1) assert DiracDelta(x, 1).diff(x) == DiracDelta(x, 2) assert DiracDelta(x).is_simple(x) is True assert DiracDelta(3*x).is_simple(x) is True assert DiracDelta(x**2).is_simple(x) is False assert DiracDelta(sqrt(x)).is_simple(x) is False assert DiracDelta(x).is_simple(y) is False assert DiracDelta(x*y).expand(diracdelta=True, wrt=x) == DiracDelta(x)/abs(y) assert DiracDelta(x*y).expand(diracdelta=True, wrt=y) == DiracDelta(y)/abs(x) assert DiracDelta(x**2*y).expand(diracdelta=True, wrt=x) == DiracDelta(x**2*y) assert DiracDelta(y).expand(diracdelta=True, wrt=x) == DiracDelta(y) assert DiracDelta((x - 1)*(x - 2)*(x - 3)).expand(diracdelta=True, wrt=x) == ( DiracDelta(x - 3)/2 + DiracDelta(x - 2) + DiracDelta(x - 1)/2) assert DiracDelta(2*x) != DiracDelta(x) # scaling property assert DiracDelta(x) == DiracDelta(-x) # even function assert DiracDelta(-x, 2) == DiracDelta(x, 2) assert DiracDelta(-x, 1) == -DiracDelta(x, 1) # odd deriv is odd assert DiracDelta(-oo*x) == DiracDelta(oo*x) assert DiracDelta(x - y) != DiracDelta(y - x) assert signsimp(DiracDelta(x - y) - DiracDelta(y - x)) == 0 assert DiracDelta(x*y).expand(diracdelta=True, wrt=x) == DiracDelta(x)/abs(y) assert DiracDelta(x*y).expand(diracdelta=True, wrt=y) == DiracDelta(y)/abs(x) assert DiracDelta(x**2*y).expand(diracdelta=True, wrt=x) == DiracDelta(x**2*y) assert DiracDelta(y).expand(diracdelta=True, wrt=x) == DiracDelta(y) assert DiracDelta((x - 1)*(x - 2)*(x - 3)).expand(diracdelta=True) == ( DiracDelta(x - 3)/2 + DiracDelta(x - 2) + DiracDelta(x - 1)/2) raises(ArgumentIndexError, lambda: DiracDelta(x).fdiff(2)) raises(ValueError, lambda: DiracDelta(x, -1)) raises(ValueError, lambda: DiracDelta(I)) raises(ValueError, lambda: DiracDelta(2 + 3*I)) def test_heaviside(): assert Heaviside(-5) == 0 assert Heaviside(1) == 1 assert Heaviside(0) == S.Half assert Heaviside(0, x) == x assert unchanged(Heaviside,x, nan) assert Heaviside(0, nan) == nan h0 = Heaviside(x, 0) h12 = Heaviside(x, S.Half) h1 = Heaviside(x, 1) assert h0.args == h0.pargs == (x, 0) assert h1.args == h1.pargs == (x, 1) assert h12.args == (x, S.Half) assert h12.pargs == (x,) # default 1/2 suppressed assert adjoint(Heaviside(x)) == Heaviside(x) assert adjoint(Heaviside(x - y)) == Heaviside(x - y) assert conjugate(Heaviside(x)) == Heaviside(x) assert conjugate(Heaviside(x - y)) == Heaviside(x - y) assert transpose(Heaviside(x)) == Heaviside(x) assert transpose(Heaviside(x - y)) == Heaviside(x - y) assert Heaviside(x).diff(x) == DiracDelta(x) assert Heaviside(x + I).is_Function is True assert Heaviside(I*x).is_Function is True raises(ArgumentIndexError, lambda: Heaviside(x).fdiff(2)) raises(ValueError, lambda: Heaviside(I)) raises(ValueError, lambda: Heaviside(2 + 3*I)) def test_rewrite(): x, y = Symbol('x', real=True), Symbol('y') assert Heaviside(x).rewrite(Piecewise) == ( Piecewise((0, x < 0), (Heaviside(0), Eq(x, 0)), (1, True))) assert Heaviside(y).rewrite(Piecewise) == ( Piecewise((0, y < 0), (Heaviside(0), Eq(y, 0)), (1, True))) assert Heaviside(x, y).rewrite(Piecewise) == ( Piecewise((0, x < 0), (y, Eq(x, 0)), (1, True))) assert Heaviside(x, 0).rewrite(Piecewise) == ( Piecewise((0, x <= 0), (1, True))) assert Heaviside(x, 1).rewrite(Piecewise) == ( Piecewise((0, x < 0), (1, True))) assert Heaviside(x, nan).rewrite(Piecewise) == ( Piecewise((0, x < 0), (nan, Eq(x, 0)), (1, True))) assert Heaviside(x).rewrite(sign) == \ Heaviside(x, H0=Heaviside(0)).rewrite(sign) == \ Piecewise( (sign(x)/2 + S(1)/2, Eq(Heaviside(0), S(1)/2)), (Piecewise( (sign(x)/2 + S(1)/2, Ne(x, 0)), (Heaviside(0), True)), True) ) assert Heaviside(y).rewrite(sign) == Heaviside(y) assert Heaviside(x, S.Half).rewrite(sign) == (sign(x)+1)/2 assert Heaviside(x, y).rewrite(sign) == \ Piecewise( (sign(x)/2 + S(1)/2, Eq(y, S(1)/2)), (Piecewise( (sign(x)/2 + S(1)/2, Ne(x, 0)), (y, True)), True) ) assert DiracDelta(y).rewrite(Piecewise) == Piecewise((DiracDelta(0), Eq(y, 0)), (0, True)) assert DiracDelta(y, 1).rewrite(Piecewise) == DiracDelta(y, 1) assert DiracDelta(x - 5).rewrite(Piecewise) == ( Piecewise((DiracDelta(0), Eq(x - 5, 0)), (0, True))) assert (x*DiracDelta(x - 10)).rewrite(SingularityFunction) == x*SingularityFunction(x, 10, -1) assert 5*x*y*DiracDelta(y, 1).rewrite(SingularityFunction) == 5*x*y*SingularityFunction(y, 0, -2) assert DiracDelta(0).rewrite(SingularityFunction) == SingularityFunction(0, 0, -1) assert DiracDelta(0, 1).rewrite(SingularityFunction) == SingularityFunction(0, 0, -2) assert Heaviside(x).rewrite(SingularityFunction) == SingularityFunction(x, 0, 0) assert 5*x*y*Heaviside(y + 1).rewrite(SingularityFunction) == 5*x*y*SingularityFunction(y, -1, 0) assert ((x - 3)**3*Heaviside(x - 3)).rewrite(SingularityFunction) == (x - 3)**3*SingularityFunction(x, 3, 0) assert Heaviside(0).rewrite(SingularityFunction) == S.Half